Delimit / De-limit: Barbara Guest at Kandinsky’s Window - Coase, Hal (Text Matters: A Journal of Literature, Theory and Culture, 2023)
This essay reads Barbara Guest’s poem “The View from Kandinsky’s Window” from her 1989 collection Fair Realism alongside Wassily Kandinsky’s own theories of form and abstraction. It argues that Guest’s poetic reinvention of historic avant-garde aesthetics on the page can be taken as an exemplary case for new feminist theorizing of the avant-garde as a set of decentered, provisional, and heterogenous practices. Guest’s engagement with Kandinsky is initially situated in the context of Clement Greenberg’s criticisms of the painter throughout the 1940s. According to Greenberg’s formalism, Kandinsky is shown to have “failed” due to his provincialism, eclecticism, and disharmonizing of scale. Guest’s poem can be seen as valuing and accentuating each of these qualities and in so doing it presents a subtle defence of Kandinsky’s aesthetics and becomes an example of the kind of intermedia contamination which Greenberg’s theorizing on “pure” modernist painting had attempted to delimit. Guest’s counter interest in “de-limiting” the work of art—removing boundaries imposed by period, style, and media—is contextualized within debates on the “limit” within avant-garde aesthetics.